The signalling pathways of interleukin-6 and gamma interferon converge by the activation of different transcription factors which bind to common responsive DNA elements. - Yuan, J (1994)
Interleukin-6 (IL-6) and gamma interferon (IFN-gamma) induce a partially overlapping set of genes, including the genes for interferon regulatory factor 1 (IRF-1), intercellular adhesion molecule 1 (ICAM-1), and the acute-phase protein alpha 2-macroglobulin. We report here that the rat alpha 2-macroglobulin promoter is activated by IFN-gamma in human hepatoma (HepG2) cells and that the IFN-gamma response element maps to the same site previously defined as the acute-phase response element (APRE), which binds the IL-6-activated transcription factor APRF (acute-phase response factor). As was reported for fibroblasts, the IFN-gamma-regulated transcription factor GAF is phosphorylated at tyrosine after IFN-gamma treatment of HepG2 cells. IFN-gamma posttranslationally activates a protein which specifically binds to the alpha 2-macroglobulin APRE. This protein is shown to be identical or closely related to GAF. Although APRF and GAF are shown to represent different proteins, their binding sequence specificities are very similar. APRF and GAF bind equally well to the APRE sequences of various acute-phase protein genes as well as to the IFN-gamma response elements of the IRF-1, ICAM-1, and other IFN-gamma-inducible genes. Transient transfection analysis revealed that the IFN-gamma response elements of the IRF-1 and ICAM-1 promoters are able to confer responsiveness to both IFN-gamma and IL-6 onto a heterologous promoter. Therefore, APRF and GAF are likely to be involved in the transcriptional induction of these immediate-early genes by IL-6 and IFN-gamma, respectively. Taken together, these results demonstrate that two functionally distinct hormones, IL-6 and IFN-gamma, act through common regulatory elements to which different transcription factors sharing almost the same sequence specificity bind.